Impact of extreme weather events on circulatory system disease mortality in Changsha city: 2015 - 2019 - Wentao KUANG; Jin ZHAO; Han NI; Piaoyi LUO; Haoyun DAI; Xiang REN; Shanghui YI; Xiuqin HONG; Wenting ZHA; Yuan LÜ (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the impact of extreme weather events on circulatory system disease mortality among residents in Changsha city , Hunan province from 2015 through 2019 for providing evidence to prevention and control and early warning of circulatory system diseases. Methods Daily number of circulatory disease mortality among residents of Changsha city were collected from Changsha Municipal Center for Disease Control and Prevention for the period of 2015 - 2019. Population data and meteorological data of the same period were simultaneously collected from Hunan Provincial Bureau of Statistics and China Meteorological Data Network. The association of extreme weather events with circulatory disease mortality in the population was analyzed with U-test of Poisson distribution, Spearman correlation analysis and single lag effect analysis. ResultsFollowing extreme weather events were identified during the 5 year period for the city: 72 low temperature and cold wave events occurring in winter season (between January and February and December of each year), 14 heatwave events in summer season (between July and August of each year), and 21 rainy and sunless weather events occurring throughout a year. During the period, totally 123 626 circulatory disease deaths were reported in the city, including 9 865, 5 286 and 14 093 deaths occurred under extreme weather conditions of low temperature and cold wave, high temperature and heat wave, and rainy and sunless weather, respectively. The daily total number of circulatory disease mortality was positively correlated with the occurrence of low temperature and cold wave (r = 0.138), high temperature and heat wave (r = 0.114), and sunless weather (r = 0.097) (all P < 0.01). The lag effect of high temperature and heat wave and rainy and sunless weather on daily number of circulatory disease mortality was not obvious. There was a single-lag effect of low temperature and cold wave on daily number of circulatory disease mortality, with a strong effect at lag day 2 - lag day 4 and the strongest hysteresis effect at lag day 2 (cross-correlation coefficient = 0.161). The single-lag effect of daily minimum temperature in cold season on daily number of circulatory disease mortality was the most obvious and the effect was the strongest at lag day 7 (correlation coefficient = - 0.518). The effect of low temperature and cold wave was the most obvious at lag day 2. ConclusionFrom 2015 to 2019, extreme weather events in Changsha were associated with circulatory disease mortality, among which low temperature and cold snaps had the greatest impact, and there was a significant single-day lag effect on daily number of circulatory disease mortality.